Fractional factorial analysis for identifying significant factors in extraction of jacalin from jackfruit seeds using anionic reverse micellar system - Sharifah Fathiyah, Sy Mohamad; Farhan, Mohd Said; Mimi Sakinah, A. M.; Shahril, Mohamad; Wan Azizi, Wan Sulaiman
Reverse micellar extraction is emerging as one of the most reliable methods for extraction and purification of various proteins and enzymes. In this study, a fractional factorial design was used to identify the significant factors having the largest effects on the forward extraction process of jacalin using reverse micelles formed by an anionic surfactant, sodium bis(2-ethylhexyl) sulfosuccinate (AOT). Effect of five different factors, namely the aqueous phase pH, surfactant (AOT) concentration, salt (NaCl) concentration, contact time and the volume ratio of organic to aqueous phase on the forward extraction efficiency were investigated using the 25-1 fractional factorial design. The results showed that only the aqueous phase pH, NaCl concentration and concentration of AOT had significant effects on the forward extraction efficiency of jacalin into AOT reverse micelles. Results obtained indicated that the fractional factorial design was a useful method for screening many process factors with a minimum number of experiments.